Chemistry: inorganic qualitative analysis in the laboratory - Metz, Clyde R. (Academic Press, 1980)
Chemistry: Inorganic Qualitative Analysis in the Laboratory is a textbook dealing with qualitative analysis in the laboratory, as well as with the process of anion and cation analysis. The book presents an overview of the subject of inorganic qualitative analysis, including as the equipment, reagents, and procedures that are going to be used in the laboratory. Preliminary experiments include the classification of precipitates, handling precipitates, separation techniques, flame tests, Brown ring test, solvent extraction. The text also describes in detail how to prepare the experiment for anion.